Innovative strategies in design of transition metal-based catalysts for large-current-density alkaline water/seawater electrolysis. (September 2022) - Zhou, Qian; Liao, Liling; Zhou, Haiqing; Li, Dongyang; Tang, Dongsheng; Yu, Fang
Abstract: Electrocatalytic water splitting for generating green hydrogen is regarded as one of the most promising pathways to change the global energy structure and achieve the global mission of carbon neutrality. Despite ever-increasing research progress at low current densities (<100 mA cm −2 ) in laboratory, the water electrolysis still faces several challenges under industrially-relevant current densities (≥200 mA cm −2 ), such as corrosion, catalyst activity and stability issues. Thus, pursuing and designing cost-effective electrocatalysts with superior activity and stability under large current density is crucial for large-scale water splitting. This review first summarizes the fundamentals of water electrolysis both in alkaline freshwater and seawater and approaches for evaluating catalytic activity. Then, it concentrates on the innovative strategies for rational design of non-noble electrocatalysts toward alkaline water splitting and direct seawater splitting. Finally, the challenges and opportunities are highlighted for the development of catalysts toward large-current-density alkaline freshwater/seawater electrolysis. Graphical abstract: Image 1 Highlights: This review summarizes the fundamentals of water electrolysis both in alkaline water and seawater and approaches for evaluating catalytic performance. This review concentrates on the innovative strategies for design of electrocatalysts toward alkaline water splitting and direct seawater splitting at large current density. The challenges and opportunities are highlighted for the development of catalysts toward large-current-density alkaline water/seawater electrolysis.